Effect of Chemical Oxidation Routes on the Properties of Chitosan- MWCNT Nanocomposites - Sánchez, Alejandro G.; Prokhorov, Evgen; Luna-Barcenas, Gabriel; Kovalenko, Yuriy; Rivera-Muñoz, Eric M.; Raucci, Maria G.; Buonocore, Giovanna (Current Nanoscience, 2019)
Background: Chitosan-multiwall carbon nanotubes (CS-MWCNTs) nanocomposites are an attractive material due to their biocompatibility and possibility to produce nanocomposites with high conductivities and high mechanical properties. Both electrical and mechanical properties depend upon the method of MWCNT chemical oxidation; this oxidation affects the interaction of CS side groups with MWCNT’s surface groups. However, in the literature, there are no reports on how different methods of MWCNT oxidation will affect the electrical and mechanical properties of related nanocomposites. Objective: The objective of this work is to probe CS-MWCNT nanocomposite’s electrical and mechanical properties by taking advantage of the presence of interfacial layer and its dependence on the methods of MWCNTs chemical oxidation routes. Methods: Nanocomposites are prepared with non-functionalized MWCNT and functionalized MWCNTs obtained by chemical oxidation treatments in HNO3 in H2SO4/NHO3 mixtures and commercially carboxyl-terminated MWCNTs, respectively. Properties of MWCNTs and nanocomposites were evaluated using SEM, FTIR, Raman, TGA, XRD, impedance and mechanical measurements. Results: It was shown that different chemical oxidation routes produce MWCNTs with a different number of carboxylic groups and defects which influence the interaction between MWCNTs with CS matrix and thickness of the interfacial layer between MWCNTs and CS matrix. Additionally, it was shown that the formation of the interfacial layer dominates on the dispersion of MWCNTs and affects on the electrical and mechanical percolation effects. Conclusion: It was shown that contrary to many studies previously reported, good dispersion of MWCNT does not guarantee obtained nanocomposites with the best electrical and mechanical properties.
Keywords: carbon nanotubes